Intergovernmental Grants and Public Expenditures: Evidence from a Survey Experiment. Issue 2 (3rd March 2016) - Baekgaard, Martin; Kjaergaard, Marie
Abstract: The relationship between intergovernmental grants and public expenditures is one of the most studied phenomena in the local public finance literature. However, little is known about whether the impact of unconditional grants is fundamentally different from that of other sources of municipal revenue. We study this question by means of a large-scale randomised survey experiment among Danish local politicians, which allows for a comparison of the impact of changes in various sources of municipal revenue. Our findings challenge the conventional conception in the public finance literature that money works differently depending on which sector they are generated in. Instead, ideology plays an important role in explaining how local politicians want to allocate resources when faced with changes in local government revenue.